Synthesis and Characterization of Chitosan-Silica Membranes for Treating Hotel Wastewater Treatment as Affected by Mass of Poly Ethylene Glycol and Poly Vinyl Alcohol - Jhon Armedi Pinem; Dessy Natalia Indah Panjaitan; M. Rifai Siregar; Edy Saputra; Syamsu Herman (Journal of Applied Materials and Technology, 2019)
Chitosan-Silica blended membranes were an attractive choice for the purification process because their porous size and morphology provide higher selectivity. In this study, the synthesis and characterization of chitosan-silica membranes were carried out with a mass variation of Poly Ethylene Glycol (PEG): 0,5; 2,5; 5 grams, Poly Vinyl Alcohol (PVA): 1, 2, 3 grams; and pressure 1, 2, 3 bars for the hotel wastewater treatment. The purpose of this study was to determine the characterization of chitosan-silica membranes obtained by SEM and tensile strength, and to determine the performance of membrane against the flux and rejection test with the effect of a mixture of PEG and PVA mass using raw materials in form of chitosan-silica. Tensile strength analysis showed that membrane with the highest tensile strength was 19,14 Mpa for PEG and 13,7 Mpa for PVA. The SEM test results showed a relatively small pore size of PEG 0,5 gram (0,061 ?m) and PVA 2 grams (0,0284 ?m). Flux and rejection results showed that membrane with 2,5 grams composition of PEG was the most effective in performance with the flux 18,19 L/m2.h and rejection elimination of BOD (50,76%), COD (46,09%) and TSS (48,00%). On the other hand, flux results showed that membrane with 3 grams composition of PVA was the most effective with the flux 20,13 L/m2.h and rejection elimination of BOD (62,84%), COD (64,73%) and TSS (38,40%). The characteristics of permeability, selectivity, and membrane pore statistics show that the silica membrane is an ultrafiltration membrane.